Differentiation of first trimester cytotrophoblast to extravillous trophoblast involves an epithelial–mesenchymal transition. Issue 12 (December 2015) - DaSilva-Arnold, Sonia; James, Joanna L.; Al-Khan, Abdulla; Zamudio, Stacy; Illsley, Nicholas P.
Abstract: The transformation of cytotrophoblast (CTB) to extravillous trophoblast (EVT) is an essential process for placental implantation. EVT generated at the tips of the anchoring villi migrate away from the placenta and invade the endometrium and maternal spiral arteries, where they modulate maternal immune responses and remodel the arteries into high-volume conduits to facilitate uteroplacental blood flow. The process of EVT differentiation has several factors in common with the epithelial-to-mesenchymal transition (EMT) observed in embryonic development, wound healing and cancer metastasis. We hypothesized that the generation of invasive EVT from CTB was a form of EMT. We isolated paired CTB and EVT from first trimester placentae, and compared their gene expression using a PCR array comprising probes for genes involved in EMT. Out of 84 genes, 24 were down-regulated in EVT compared to CTB, including epithelial markers such as E-cadherin (−11-fold) and occludin (−75-fold). Another 30 genes were up-regulated in EVT compared to CTB including mesenchymal markers such as vimentin (235-fold) and fibronectin (107-fold) as well as the matrix metalloproteinases, MMP2 and MMP9 (357-fold, 129-fold). These alterations also included major increases in the ZEB2 (zinc finger E-box binding homeobox 2, 198-fold) and TCF4 (transcription factor 4, 18-fold) transcription factors, suggesting possible stimulatory mechanisms. There was substantial up-regulation of the genes encoding TGFβ1 and TGFβ2 (48-fold, 115-fold), which may contribute to the maintenance of the mesenchymal-like phenotype. We conclude that transformation of CTB to EVT is consistent with an EMT, although the differences with other types of EMT suggest this may be a unique form. Highlights: Cyto- and extravillous trophoblast were isolated from first trimester human placenta. Expression was compared for genes associated with the epithelial–mesenchymal transition. Out of 84 genes examined, 30 were up-regulated and 24 were down-regulated. The alterations in gene expression are consistent with an epithelial–mesenchymal transition.